Improve speaking skills with Duolingo’s mobile game-based language learning - Kazu, Ibrahim Yasar; Kuvvetli, Murat (Asian Journal of Education and Training, 2024)
The purpose of this research is to evaluate the effectiveness of Duolingo's game-based methodology in improving speaking proficiency within mobile language learning, while also examining the specific attributes and strategies contributing to its success and exploring implications for language education and learner optimization. Given the growing prevalence of mobile language learning platforms, the research meticulously scrutinizes the specific attributes and strategies employed by Duolingo that contribute to the refinement of oral fluency. This study employs a mixed methods design, integrating phenomenological and experimental approaches through a pre, post and attainment speaking tests with a control group design supported with metaphorical perceptions. The findings underscore the pivotal role of assimilating technological advancements and gamified pedagogical approaches within language education to expedite effective intercultural communication across multifarious linguistic landscapes. Furthermore, the results emphasize the importance of continuously adapting language learning methodologies to leverage emerging technologies and gamification strategies in order to foster effective communication skills in diverse linguistic contexts. The implications for prospective inquiries advocate for longitudinal investigations delving into the enduring implications of mobile game-based language learning on comprehensive linguistic acquisition, necessitating comparative inquiries to ascertain the comparative efficacy of diverse mobile applications in fostering distinct language proficiencies. Additionally, probing the influence of individual learner attributes and predilections in optimizing the utilization of mobile language learning applications could yield valuable insights for tailoring language acquisition paradigms.